Stewardship of the Built Environment Sustainability, Preservation, and Reuse - Young, Robert A.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2012)
When we think of green building, we tend to picture new construction. But Robert A. Young argues that the greenest building is often the one that has already been built. In Stewardship of the Built Environment, he shows how rehabilitating and reusing existing structures holds untapped potential for achieving sustainable communities. Students and professionals alike will discover the multifaceted benefits of reuse. Young begins by describing how historic preservation in the United States, often overlooked because of the predominant focus on new construction, is actually an important sustainable design strategy. He then examines the social, environmental, and economic benefits of preservation$1 (Bfrom the societal value of reusing existing buildings to financial incentives available for rehabilitation. Young concludes with insights into the future of reusing buildings as a sustainability strategy. He also provides several informative appendices, including a glossary of key terms and acronyms and recommendations for further reading. Readers will become familiar with essential terminology; sustainability and historic preservation metrics; government oversight processes; and opportunities for smart growth afforded by rehabilitation. This knowledge is key to preserving the past while building a sustainable future.s
Foreword -- Preface -- Acknowledgments -- 1. Overview and Introduction. Stewardship of the Built Environment. Application of SEE to the Built Environment. Social Contributions of Preservation and Reuse. Environmental Contributions of Preservation and Reuse. Economic Contributions of Preservation and Reuse. Sustainable Stewardship -- 2. Social Factors. Seeking Urbanism: Social Implications for Preservation and Reuse. Perspectives from Europe. Preservation Tools and Processes. Sociopolitical Framework. Collaborative Practice. Connecting the Dots -- 3. Environmental Factors. Environmental Indicators. Architectural Form as Environmental Control. Increasing Sustainability -- 4. Economic Factors. Economic Incentives. Economic Planning and Development Tools. Economic Indicators -- 5. Putting It All Together. Creating Community: Fort Douglas, Salt Lake City, Utah. Affirming the Environmental Contribution: Christman Company Headquarters, Lansing, Michigan. Creating an Economic Catalyst: The Old Post Office, St. Louis, Missouri. Lessons Learned. Future Directions and Imperatives -- Appendix A: Abbreviations -- Appendix B: Recommendations for Further Reading -- References -- Index.
Keywords: Environmental sciences; Architecture; Sustainable development; Environment; Sustainable Development; Cities, Countries, Regions; Building Types and Functions; Energy Efficiency (incl. Buildings).; Urbanism